VET leaders’ collaborative problem-solving skills: insights from a professionals’ master’s degree program - Trikoili, Anna; Georgiou, Despoina; Pittich, Daniel (Frontiers in Education, 2024)
Vocational education and training (VET) structures are ecosystems bound to collaboration. As VET leaders’ roles become increasingly diverse and demanding, challenges must be addressed through collaborative efforts within teams. Leaders’ collaborative problem-solving (CPS) skills remain unexplored despite the importance of CPS in VET settings. This single case study investigates the CPS skills that VET leaders use in addressing tasks and challenges in an educational setting. Postgraduate students in a professional master’s degree program with several years of work experience in VET leadership positions served as study participants. We utilised content analysis on video data of participants engaging in group work on an assignment that required them to give both constructed responses and creative solutions. The study also analysed VET leaders’ self-reflections on their CPS skills collected through a survey tool. Our results revealed that despite participants’ similar professional profiles, their performance in CPS varied significantly. Older participants seemed to have better self-reflection skills, and experienced professionals could allocate cognitive resources to more complex strategic and meta-cognitive processes. This study can be used as a roadmap for targeted professional development programs aiming to improve CPS skills and for informed decisionmaking in choosing professionals for pivotal leadership positions.